Electronic content on the internet and its role in the intellectual and ideological extension of the kharijites division and its impact on the islamic world - Yousef A. Baker, El-Ebiary; Shehata Hafez, Mohamed El Sheikh; Abdul Ghani, Md Din (2020)
The Internet is a medium, and its greatest impact is speed, as it provides speed in trading and consulting, making deals, and obtaining and exchanging information. Countries with advanced telecommunications infrastructures are more likely to have faster access and greater reliability to access the Internet.This study seeks to highlight an important aspect of scientific rooting, which is the aspect of the correct approach to reasoning, especially in matters of belief that are among the most important issues, and given the seriousness of the intellectual and ideological deviation of the group of Kharijites and the results that resulted from this thought of rupture and weakening of most Islamic countries and the spread of ideas not Its relation to the teachings of Islam is devoted to works that contradict the teachings of Islam. The research problem revolves around the seriousness of the ideological and ideological deviation on the Islamic Nation, and the role of ISIS ideology, “the thought of atonement” in the schizophrenia and fragmentation in the Islamic Nationat the present time. This study aims at examining the intellectual development of the Kharijites' thought in the modern era, and clarifying the idea of the historical link between Kharij’s thought in the past and the resurrection of Kharij’s thought again for reasons that we will show in the research. Other in the modern era, and among the results of the research that the intellectual deviation in the Islamic Nation was the result of the dimension of the approaches to inference from the true belief and hyperbole in the use of reason to interpret texts, and that the ideas that are on the scene now are nothing but extension and compatibility and similarity with the thought of the Kharijites and derive from it their ideological origins Such as expiation of the owners of major sins, ignorance of society and excessive debt.